2018
DOI: 10.1111/joor.12633
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychotropic medications and presence of sleep bruxism: A systematic review

Abstract: The purpose of this study was to systematically review the literature for studies that investigated the association between use of psychotropic medications and presence of sleep bruxism (SB). Observational studies were selected in a two-phase process. Searches were performed on six electronic databases, and a grey literature search was conducted on three databases. SB diagnosis was based on questionnaires or clinical examinations; no polysomnography examinations were performed. Risk of bias was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 34 publications
0
81
0
11
Order By: Relevance
“…Furthermore, with regard to confounding factors, it is suggested that some comorbidities such as depression and stress, use alcohol, caffeine or tobacco, and even some psychotropic medications might be positively associated with SB, which may hinder the evaluation of an association between SB and anxiety in particular. Moreover, it is worth mentioning that the literature is sparse about the possible role of SB on the different disorders of the anxiety spectrum…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with regard to confounding factors, it is suggested that some comorbidities such as depression and stress, use alcohol, caffeine or tobacco, and even some psychotropic medications might be positively associated with SB, which may hinder the evaluation of an association between SB and anxiety in particular. Moreover, it is worth mentioning that the literature is sparse about the possible role of SB on the different disorders of the anxiety spectrum…”
Section: Discussionmentioning
confidence: 99%
“…Overall, three SR investigated prevalence rates among different populations, seventeen investigated associated factors, six evaluated effects on stomatognathic structures, two evaluated diagnostic accuracy of bruxism assessment tools, and thirteen assessed interventions' effectiveness . Statistical pooling of data using MA was available in 7 studies .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, nine SR were judged with low risk, seventeen with moderate risk and fifteen with high risk of bias . Major concerns regarding risk of bias were observed, which included the following: (a) lack of a priori registration of the study protocol; (b) inappropriate range of database/electronic sources searched; (c) no risk of bias assessment; (d) study selection, data collection or bias assessment performed by only one reviewer; (e) no publication bias assessment or sensitivity analysis; (f) high risk of bias in included primary studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations